Presentation skills for students - Becker, Lucinda; Van Emden, Joan (New York Palgrave Macmillan, 2004)
A practical, useful guide for all students in further or higher education. Topics covered include speaking effectively in seminars and tutorials, delivering formal presentations and succeeding at a job interviews. Regular checklists and the friendly, down to earth style make this an ideal reference tool.